Analysis Quality Control of Creamer Product Packaging using DMAIC and RCA Methods - Qodir Umrin, Abdul; Catur Wahyuni, Hana (International Journal on Orange Technologies, 2025)
This study aims to analyze the types of defects in the packaging process of creamer products and provide suggestions for improvements to the company based on the results of data processing that has been carried out with two methods to explain the material, energy, capital, and total losses. The method used involves calculating the sigma index with several tools such as pareto diagrams, fish bone diagrams to see the extent of the cause and effect, and failure tree diagrams to find out the root of the problem and in analyzing the root of the problem also involves the 5Whys method. The results of the analysis show that productivity is able to survive and be stable by needing to evaluate several factors that produce a high percentage in the analysis of product packaging process defects. Improvement proposals are addressed to the company for improvement and optimization of the results of the company.